Analysis of Sidewalk or Pedestrian Path Satisfaction - Widodo Budi Dermawan; Hanayas Bagaskara; Muhammad Isradi; Amar Mufhidin (NAROTAMA UNIVERSITY, Indonesia)
Increased mobility in DKI Jakarta area has resulted in the government having to make improvements to facilities or infrastructure especially in the transportation sector, but in the effort to increase this, the government is still siding with motorized vehicles compared to pedestrians..This study aims to determine the level of satisfaction and performance of pedestrian paths on pedestrian paths at Jalan Casablanca, South Jakarta, Kota Kasablanka Mall Area. This research method is carried out by direct survey to the research location in order to obtain pedestrian data such as the number of pedestrians, pedestrian speed, etc. Then also by distributing questionnaires to 100 respondents. The population taken in this study are people (sidewalk users) who pass or travel on foot along Jalan Casablanca, Jakarta Selata, Kota Kasablanka Mall Area. Data processing in this study used Microsoft Excel and SPSS version 24 and the methods used are Importance Performance Analysis (IPA) and Level Of Service. The results of data analysis using Importance Performance Analysis methode, it was found that the level of interest and satisfaction of pedestrians in Quadrant I which is given priority is the availability of facilities for the disabled and the elderly, order on pedestrian paths (street vendors, illegal parking, etc.), smooth travel, ease of walking. on the sidewalk, availability of trash cans. In Quadrant II what must be maintained are having lighting, paving conditions (not cracked / perforated, not slippery, etc.), sidewalk cleanliness, having traffic signs, having a barrier between the sidewalk and the road, adequate drainage channels, availability of stops / shelters, availability JPO (Pedestrian Bridge). In Quadrant III, the low priority is the availability of public telephones, availability of seats, neatness and regularity of the sidewalks. And in Quadrant IV, which is categorized as excessive, there is a sidewalk width of at least 3 meters, sidewalk slope (easily accessible), availability of shade trees, and accessibility between modes of public transportation. The results of the analysis of the road level with the LOS method get the LOS A category for the pedestrian space level. Then for the average pedestrian speed get the LOS B level on Monday and LOS C on Friday and Saturday. Then for the flow level get the LOS A category. And finally for the ratio assessment level get LOS A.